1155 Surgical Ligation of Patent Ductus Arteriosus in Preterms Less Than 30 Weeks Gestation in a Tertiary Neonatal Unit. (October 2012) - Kumar, R; Podugu, L; Rasiah, SV
Abstract : Background: Patent ductus arteriosus is inversely related to gestational age. It remains a significant morbidity and challenge to manage in extremely preterm babies. Medical therapy reduces the need for surgical ligation. Aim: To audit our management of PDA and the need for surgical ligation. Methods: The Badger database was interrogated for babies less than 30+0 weeks gestation who had a PDA. Their management and outcomes were audited over a 3 year period from 01/04/09 to 31/03/12. Results: In the last 3 years, there were 300 babies less than 30+0 weeks gestation who were admitted to our tertiary neonatal unit. PDA was confirmed on echocardiography in 190 (63%) babies. 72 (38%) babies were treated with Indomethacin (62 complete and 10 incomplete course: 5 renal impairment, 3 thrombocytopenia and 2 NEC). 25 (13%) babies had a surgical ligation of their PDA (The median gestational age at birth was 24 weeks and median birth weight was 725 grams). 13 (52%) babies who underwent ligation, received at least one complete course of Indomethacin. Median age at ligation was 30 days of life. There was no surgical morbidity or mortality from the PDA ligation. 67 babies died and 233 babies were discharged home. 25 babies needed home oxygen of which 21 previously had a significant PDA. Conclusion: Despite medical therapy, there is a small population of extremely preterm babies who have a recalcitrant PDA that need surgical ligation. Early identification with serial echocardiography and proactive management of these babies might improve their respiratory morbidities.